Past, present, and future options for right ventricular outflow tract reconstruction - Carrel, Thierry (Frontiers in Surgery, 2023)
The pulmonary valve is the most frequently replaced cardiac valve in congenital heart diseases. Whether the valve alone or part of the right ventricular outflow tract have to be repaired or replaced depends on the specific pathological anatomy of the malformation. Once the decision to replace the pulmonary valve has been made, two options are available: the isolated transcatheter pulmonary valve replacement and the surgical implantation of a prosthetic valve either isolated or in combination with a procedure on the right ventricular outflow tract. In this paper, we will focus on the different past and present surgical options and present a new concept called "endogenous tissue regeneration", a promising alternative to the hitherto existing implants. From a general point of view, neither the transcatheter nor the surgical valvular implants are magic bullets in the arsenal for the management of valvular diseases. Smaller valves have frequently to be replaced because of outgrowth of the patients, larger tissue valves may present late structural valve deterioration, while xenograft and homograft conduits may calcify and therefore narrow within unpredictable incidence and interval following implantation. Based on long-term research efforts combining the knowledge of supra-molecular chemistry, electro-spinning and regenerative medicine, endogenous tissue restoration has emerged most recently as a promising option to create long-term functioning implants. This technology is appealing because following resorption of the polymer scaffold and timely replacement through autologous tissue, no foreign material remain at all in the cardiovascular system. Proof of concept studies as well as small first in man series have been completed and have demonstrated favorable anatomic and hemodynamic results, comparable to currently available implants in the short-term. Based on the initial experience, important modifications to improve the pulmonary valve function have been initiated.